A review on Labeo calbasu (Hamilton) with an emphasis on its conservation - Sandipan Gupta; Samir Banerjee (Journal of Fisheries, 2015)
Labeo calbasu is a freshwater fish species and is the most important carp species next to three Indian Major Carps Labeo rohita, Catla catla and Cirrhinus mrigala. It is a popular food fish and also is admired as a sport fish. Recently this fish species has also made its entry in ornamental fish markets of India and abroad. In last few years, the natural populations of this fish species has seriously declined due to over fishing and other anthropological reasons. In India it has been reported as Lower Risk near Threatened and in Bangladesh as endangered species. Earlier number of works has been conducted on different aspects of Labeo calbasu including food and feeding habit and reproductive biology. This report has been prepared with a view to sum up all those previously documented information along with pointing out the missing information further study of which will be beneficial for its fishery. Apart from this, it has been tried to note down some possible measures which should be considered for its conservation.